Big Gods, historical explanation, and the value of integrating the history of religion into the broader academy - Slingerland, Edward G. (Religion, 2015)
This article discusses critiques raised by historians of religion concerning Ara Norenzayan's Big Gods: How Religion Transformed Cooperation and Conflict (Princeton: Princeton University Press, 2013), offering some defense of Norenzayan's position, but also discussing in detail the more substantive challenges. It concludes with some reflections on the current position of the history of religion within the Academy, and an argument for why large-scale explanatory projects and interdisciplinary collaboration should be part of the future of our field.